Quality indicators of professional practice of nurses - Joana Vieira; Margarida Reis Santos; Regina Pires; Filipe Pereira (Instituto Politécnico de Viseu, 2021)
Introduction: Quality in health is one of the key requirements that clients demand. To improve their practice nurses use quality indicators as an important strategy for assessment and changes in care. Objective: To identify the indicators that nurses of Integrated Continuous Care at Home Teams consider adequate to monitor the quality of their professional practice in the ambit of the caregiver. Methods: Qualitative, descriptive and cross-sectional study. Data collection using a semi-structured interview, recorded in audio, to a focus group of 11 nurses. The information was analyzed using Bardin's content analysis technique. Results: Identified 32 indicators, related to the acquisition of cognitive and instrumental skills necessary to meet the needs of the dependent person in self-care. Conclusion: The identified indicators are related to the process and outcomes of the Donabedian's triad and highlights the importance of using a standardized terminology in nursing.